2021
DOI: 10.1016/j.jhepr.2020.100191
|View full text |Cite
|
Sign up to set email alerts
|

Obeticholic acid is associated with improvements in AST-to-platelet ratio index and GLOBE score in patients with primary biliary cholangitis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…As one of the FXR agonists, obeticholic acid (OCA) significantly reduces alkaline phosphatase (ALP), gamma glutamyltranspeptidase (GGT), and alanine aminotransferase (ALT) levels in patients with primary biliary cirrhosis who do not respond to ursodeoxycholic acid [270] . Long-term OCA treatment in patients with primary biliary cholangitis (PBC) shows improvements or stabilizations of disease features, including ductular injury, fibrosis, and collagen morphometry [271][272][273][274][275] .…”
Section: Supervised Pep Anti-fibrosis Anti-cirrhosismentioning
confidence: 99%
“…As one of the FXR agonists, obeticholic acid (OCA) significantly reduces alkaline phosphatase (ALP), gamma glutamyltranspeptidase (GGT), and alanine aminotransferase (ALT) levels in patients with primary biliary cirrhosis who do not respond to ursodeoxycholic acid [270] . Long-term OCA treatment in patients with primary biliary cholangitis (PBC) shows improvements or stabilizations of disease features, including ductular injury, fibrosis, and collagen morphometry [271][272][273][274][275] .…”
Section: Supervised Pep Anti-fibrosis Anti-cirrhosismentioning
confidence: 99%
“…The "normalisation" of aminotransferases, especially using more stringent criteria to define the healthy ranges, might be a debatable end-point, and more so since response to treatment is assessed on decrease and normalization of ALP levels [10]. However, aminotransferases are part of validated prognostic scores to predict patients' outcome, and more recently a secondary analysis of OCA registration study data showed that treatment with OCA is also associated in an improvement in the aspartate aminotransferase-toplatelet ratio index (APRI), besides improvement in GLOBE score, thus emphasizing how (successful) response to treatment may also include the evaluation of hepatic necroinflammatory activity [25].…”
Section: Discussionmentioning
confidence: 99%
“… 62 A post hoc analysis by Harms et al in the POISE study reported that 12 months of OCA treatment resulted in the reduction of APRI and GLOBE scores. 63 They reported that in patients who had GLOBE score >0.3 at baseline, the use of OCA 5-1 mg was associated with a greater percentage of patients achieving a GLOBE score <0.3, compared to placebo (27% vs 6%). Furthermore, a lower proportion of patients in the OCA treated group with GLOBE score≤0.3 at baseline were noted to progress to GLOBE score >0.3, compared to placebo (3–13% vs 33%).…”
Section: Approved Treatments and The Risk Stratification Scoresmentioning
confidence: 99%